A novel hand exoskeleton to enhance fingers motion for tele-operation of a robot gripper with force feedback☆. (February 2022) - Amirpour, Ehsan; Fesharakifard, Rasul; Ghafarirad, Hamed; Rezaei, Seyed Mehdi; Saboukhi, Alireza; Savabi, Mohammad; Gorji, Masoud Rahimi
Abstract: This research describes a robotic system's design, optimization, and implementation processes for tele-operation with haptic feedback using the Hand Exoskeleton of New technologies research center (HEXON) as a novel haptic mechanism and the HEXON robotic gripper to work collaboratively with the exoskeleton. In particular, a force-sensitive robotic gripper is connected to a hand exoskeleton, mimics the user's hand movements, and transfers haptic feedback through the exoskeleton. The two-finger exoskeleton's design process consists of a multi-criteria optimization procedure to simultaneously maximize applied force to the finger and workspace of the attached exoskeleton, optimizing both the Perpendicular Impact Force (PIF) and the Global Isotropy Index (GII), considering worst-case collision avoidance. Due to the tele-operation application and using a robotic arm as a slave in the remote scenario, the gripper can be used as an end-effector for a palletizing 3-DOF robotic arm, and movement of the gripper can be achieved by using a visual sensor to pinpoint the user's hand location in 3D space. With the aim of the stress analysis software, the exoskeleton and gripper designs were analyzed to evaluate the system strength against applied forces. Finally, based on the achieved results, the gripper and two-fingered exoskeleton prototypes were fabricated. Simulations and experimental results are reported, showing the potential of the HEXON in haptics and tele-operation applications, and the exoskeleton is used to operate a robotic arm and gripper while the user can perceive the objects virtually.